The OEIS mourns the passing of Jim Simons and is grateful to the Simons Foundation for its support of research in many branches of science, including the OEIS.
login
The OEIS is supported by the many generous donors to the OEIS Foundation.

 

Logo
Hints
(Greetings from The On-Line Encyclopedia of Integer Sequences!)
A156691 Triangle T(n, k, m) = t(n,m)/( t(k,m) * t(n-k,m) ) with T(n, 0, m) = T(n, n, m) = 1, where t(n, m) = Product_{j=1..n} Product_{i=1..j-1} ( 1 - (m+1)*(i+1) ) and m = 2, read by rows. 8
1, 1, 1, 1, -5, 1, 1, 40, 40, 1, 1, -440, 3520, -440, 1, 1, 6160, 542080, 542080, 6160, 1, 1, -104720, 129015040, -1419165440, 129015040, -104720, 1, 1, 2094400, 43865113600, 6755227494400, 6755227494400, 43865113600, 2094400, 1, 1, -48171200, 20177952256000, -52825879006208000, 739562306086912000, -52825879006208000, 20177952256000, -48171200, 1 (list; table; graph; refs; listen; history; text; internal format)
OFFSET
0,5
COMMENTS
Row sums are: {1, 2, -3, 82, 2642, 1096482, -1161344798, 13598189404802, 633950903882665602, 301999235305843794118402, ...}.
LINKS
FORMULA
T(n, k, m) = t(n,m)/( t(k,m) * t(n-k,m) ) with T(n, 0, m) = T(n, n, m) = 1, where t(n, m) = Product_{j=1..n} Product_{i=1..j-1} ( 1 - (m+1)*(i+1) ) and m = 2.
T(n, k, m, p, q) = (-p*(m+1))^(k*(n-k)) * (f(n,m,p,q)/(f(k,m,p,q)*f(n-k,m,p,q))) where Product_{j=1..n} Pochhammer( (q*(m+1) -1)/(p*(m+1)), j) for (m, p, q) = (2, 1, 1). - G. C. Greubel, Feb 25 2021
EXAMPLE
Triangle begins as:
1;
1, 1;
1, -5, 1;
1, 40, 40, 1;
1, -440, 3520, -440, 1;
1, 6160, 542080, 542080, 6160, 1;
1, -104720, 129015040, -1419165440, 129015040, -104720, 1;
1, 2094400, 43865113600, 6755227494400, 6755227494400, 43865113600, 2094400, 1;
MATHEMATICA
(* First program *)
t[n_, k_]:= If[k==0, n!, Product[1 -(i+1)*(k+1), {j, n}, {i, 0, j-1}] ];
T[n_, k_, m_]:= If[n==0, 1, t[n, m]/(t[k, m]*t[n-k, m])];
Table[T[n, k, 2], {n, 0, 12}, {k, 0, n}]//Flatten (* modified by G. C. Greubel, Feb 25 2021 *)
(* Second program *)
f[n_, m_, p_, q_]:= Product[Pochhammer[(q*(m+1) -1)/(p*(m+1)), j], {j, n}];
T[n_, k_, m_, p_, q_]:= (-p*(m+1))^(k*(n-k))*(f[n, m, p, q]/(f[k, m, p, q]*f[n-k, m, p, q]));
Table[T[n, k, 2, 1, 1], {n, 0, 12}, {k, 0, n}]//Flatten (* G. C. Greubel, Feb 25 2021 *)
PROG
(Sage)
@CachedFunction
def f(n, m, p, q): return product( rising_factorial( (q*(m+1)-1)/(p*(m+1)), j) for j in (1..n))
def T(n, k, m, p, q): return (-p*(m+1))^(k*(n-k))*(f(n, m, p, q)/(f(k, m, p, q)*f(n-k, m, p, q)))
flatten([[T(n, k, 2, 1, 1) for k in (0..n)] for n in (0..12)]) # G. C. Greubel, Feb 25 2021
(Magma)
f:= func< n, m, p, q | n eq 0 select 1 else m eq 0 select Factorial(n) else (&*[ 1 -(p*i+q)*(m+1): i in [0..j], j in [0..n-1]]) >;
T:= func< n, k, m, p, q | f(n, m, p, q)/(f(k, m, p, q)*f(n-k, m, p, q)) >;
[T(n, k, 2, 1, 1): k in [0..n], n in [0..10]]; // G. C. Greubel, Feb 25 2021
CROSSREFS
Cf. A007318 (m=0), A156690 (m=1), this sequence (m=2), A156692 (m=3).
Sequence in context: A367380 A322220 A174790 * A246051 A111820 A174912
KEYWORD
sign,tabl
AUTHOR
Roger L. Bagula, Feb 13 2009
EXTENSIONS
Edited by G. C. Greubel, Feb 25 2021
STATUS
approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

License Agreements, Terms of Use, Privacy Policy. .

Last modified May 28 00:20 EDT 2024. Contains 372900 sequences. (Running on oeis4.)